The Salivary Inflammatory Biomarkers (Interleukin-6, C - reactive protein) in Relation with Caries-Experience among a Group of 12 Year Old Obese Boys - Ateka R Aziz; Ahlam T Mohammed (College of Dentistry/ University of Baghdad, 2016)
Background: Obesity and dental caries are multifactorial diseases related to poor eating habits and show a close relationship with the sociodemographic characteristics of individuals presenting these diseases. This research aimed to investigate the severity of dental caries among group of obese boys aged 12 year in relation to salivary interleukin-6 (IL-6) and C-reactive protein (CRP) of unstimulated whole saliva in comparison with normal weighted boys of the same age. Materials and Methods: The study group included 40 obese boys, with an age of 12 year. The control group included 40 normal weighted boys of the same age. The total sample involved for nutritional status assessment using Body Mass Index specific for age and gender according to CDC growth chart (2000). The diagnosis and recording of dental caries conducted by using (D1-4MFS and d1-4mfs) index according to the criteria of Muhlemann (1976). The collection of unstimulated whole saliva was performed under standardized condition. Salivary samples were chemically analyzed for measuring IL-6 and CRP. Results: The caries experience among study group was lower than that among control group for both dentitions, with significant differences for D2, ds and dmfs and highly significant difference for d4. Salivary inflammatory biomarkers (IL-6, hs-CRP) were slightly higher among study group compared with control group with no significant difference between them. Salivary IL-6 and hs-CRP were negatively correlated with dental caries of both dentitions among study group with significant correlation between IL-6 and D2, while they were correlated positively with dental caries of both dentitions among control group with highly significant correlation between IL-6 and D3 and significant correlation between IL-6 and d4. Conclusion: Obesity and dental caries are associated with increased levels of salivary interleukine-6 and C-reactive protein, this making both obesity and dental caries as a state of inflammation that exacerbating immune responses in the body. Key words: Obesity, salivary cytokines, interleukine-6, C-reactive protein.